1979
DOI: 10.1039/p19790001004
|View full text |Cite
|
Sign up to set email alerts
|

Beyerane diterpenes: structure and reactivity of the α-ketol ent-3β-hydroxybeyer-15-ene-2,12-dione, its corresponding diosphenol, and synthesis of the isomeric α-ketol acetates

Abstract: In the ent-beyerane series, predominant hydride attack of a carbonyl at C-2 or C-3 from the less hindered ent-a-face is well established by analogy to similar terpenoid systems-see ref.9a.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…Compound 6 analyzed for C 20 H 26 O 3 by elemental analysis and the molecular ion at m / z 314 in its EIMS. Its physical characteristics (mp, [α] 25 D ) and spectral (IR, UV, 1 H NMR) data were identical with those reported for 2-hydroxy-1,15-beyeradiene-3,12-dione ( 6 ) isolated from A. johonsonii …”
supporting
confidence: 65%
See 2 more Smart Citations
“…Compound 6 analyzed for C 20 H 26 O 3 by elemental analysis and the molecular ion at m / z 314 in its EIMS. Its physical characteristics (mp, [α] 25 D ) and spectral (IR, UV, 1 H NMR) data were identical with those reported for 2-hydroxy-1,15-beyeradiene-3,12-dione ( 6 ) isolated from A. johonsonii …”
supporting
confidence: 65%
“…A comparison of its physical and spectral characteristics (mp, IR, UV, [α] 25 D , and 1 H NMR) with those of 2-acetoxy-1,15-beyeradiene-3,12-dione ( 5 ) proved their identity. This is the first report of its natural occurrence, although it was reported earlier as a derivative of the enol, 2-hydroxy-1,15-beyeradiene-3,12-dione ( 6 ), isolated from the plant Androstachys johnsonii Prain . However, its 13 C NMR as well as 2-D NMR data were not reported earlier and hence are presented here (see Experimental Section).…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…The three major components were: yucalexin B-9 (ent-3b-hydroxybeyer-15-en-2,12-dione), the most abundant diterpenoid component in deteriorated cassava root (10 mg/kg fresh weight), yucalexin P-8 (ent-8a,14a-epoxy-3b-hydroxypimara-9(11),15-dien-2,12-dione), an ent-pimarane, was the second most abundant diterpenoid (4 mg/kg fresh weight), and yucalexin A-19 (ent-3b,16a-dihydroxyatis-13-en-2-one), an ent-atisane, also a novel compound was the third most abundant diterpenoid (1.4 mg/ kg fresh weight). Yucalexin B-9 together with the beyeranes, yucalexin B-5 (ent-2-hydroxybeyera-1,15-dien-3,12-dione) and B-6 (ent-beyer-1,15-dien-3,12-dione) and an atisane, yucalexin A-16 (ent-16a-hydroxyatis-13-en-3-one) had been previously reported from the heartwood of Androstachys johnsonii (Piacenza et al, 1979(Piacenza et al, , 1985. Yucalexin B-9 has also been recently reported from Excoecaria agallocha together with the dihydro derivative of yuca- lexin A-16 (Kang et al, 2005).…”
Section: Terpenoidsmentioning
confidence: 94%
“…In the Picrodendraceae family, two genera (Piranhea Bail and Podocalyx Klotzch) are distributed in three Brazilian regions as in the Northern (Amapa, Amazonas, Tocantins, Acre, and Rondonia), Northeast (Maranhao and Bahia), and Center-West (Mato Grosso) [25,26]. Studies with some family species showed the class of terpenes as chemical constituents of the Picrodendraceae family, as in studies of the species Androstachys [27][28][29].…”
Section: Family Picrodendraceae Euphorbiaceae)mentioning
confidence: 99%